Discontinuation of tyrosine kinase inhibitors in chronic myeloid leukemia: Recommendations for clinical practice from the French Chronic Myeloid Leukemia Study Group. Issue 14 (3rd May 2018) - Rea, Delphine; Ame, Shanti; Berger, Marc; Cayuela, Jean‐Michel; Charbonnier, Aude; Coiteux, Valérie; Cony‐Makhoul, Pascale; Dubruille, Viviane; Dulucq, Stéphanie; Etienne, Gabriel; Legros, Laurence; Nicolini, Franck; et al.
Abstract : BACKGROUND: The ultimate goal of chronic myeloid leukemia management in the tyrosine kinase inhibitor (TKI) era for patients who obtain deep molecular responses is maintaining a durable off‐treatment response after treatment discontinuation; this situation is called treatment‐free remission (TFR). Knowledge accumulated during the last 10 years justifies moving TFR strategies from research to clinical practice. METHODS: Twenty experts from the French Chronic Myeloid Leukemia Study Group (France Intergroupe des Leucémies Myéloïdes Chroniques), including 17 hematologists, 2 molecular biologists, and 1 cytogeneticist, critically reviewed published data with the goal of developing evidence‐based recommendations for TKI discontinuation in clinical practice. RESULTS: Clinically relevant questions were addressed, including the selection of candidate patients (with known prognostic factors for outcomes taken into account), detailed monitoring procedures during the treatment‐free phase, a definition of relapse requiring therapy resumption, and monitoring after treatment reintroduction. CONCLUSIONS: This work presents consensus statements with the aim of guiding physicians and biologists by means of pragmatic recommendations for safe TKI discontinuation in daily practice. Cancer 2018;124:2956‐63. © 2018 American Cancer Society . Abstract : Clinical trials have demonstrated that patients with chronic‐phase chronic myeloid leukemia with deep and durable molecular responses can attempt to stop using tyrosine kinase inhibitors. The French Chronic Myeloid Leukemia Study Group (France Intergroupe des Leucémies Myéloïdes Chroniques) has developed recommendations for tyrosine kinase inhibitor discontinuation in daily practice.